Molecular genetic analysis of neural stem cells after space flight and simulated microgravity on earth. Issue 10 (22nd June 2021) - Han, Yilin; Zeger, Lukas; Tripathi, Rekha; Egli, Marcel; Ille, Fabian; Lockowandt, Christian; Florin, Gunnar; Atic, Edvin; Redwan, Itedale N.; Fredriksson, Robert; Kozlova, Elena N.
Abstract: Understanding how stem cells adapt to space flight conditions is fundamental for human space missions and extraterrestrial settlement. We analyzed gene expression in boundary cap neural crest stem cells (BCs), which are attractive for regenerative medicine by their ability to promote proliferation and survival of cocultured and co‐implanted cells. BCs were launched to space (space exposed cells) (SEC), onboard sounding rocket MASER 14 as free‐floating neurospheres or in a bioprinted scaffold. For comparison, BCs were placed in a random positioning machine (RPM) to simulate microgravity on earth (RPM cells) or were cultured under control conditions in the laboratory. Using next‐generation RNA sequencing and data post‐processing, we discovered that SEC upregulated genes related to proliferation and survival, whereas RPM cells upregulated genes associated with differentiation and inflammation. Thus, (i) space flight provides unique conditions with distinctly different effects on the properties of BC compared to earth controls, and (ii) the space flight exposure induces postflight properties that reinforce the utility of BC for regenerative medicine and tissue engineering. Abstract : Boundary cap neural crest stem cells as neurospheres or in 3D bioprinted scaffold were subjected to space condition in Sounding Rocket. The cells survived space flight and acquired novel post‐flight gene expression characteristics and increased proliferation capacity.